Strategies For Independent Character Development in Children With Mental Disabilities at Uswatun Hasanah Aceh Foundation: (Case Study) - Muniruddin, Muniruddin; Suyanta, Sri; Fikri, Mumtazul (Jurnal Ilmiah Teunuleh, 2025)
This study aims to examine strategies for fostering independent character in children with intellectual disabilities at the Uswatun Hasanah Orphanage in Aceh. A qualitative descriptive approach was employed, using data collection techniques such as interviews, observation, and documentation. The research subjects included the orphanage's management, caregiving teachers, and children with special needs. The findings reveal that the character development strategies involve the application of habituation, role modeling, and positive reinforcement methods. The content of character education focuses on daily religious practices, moral behavior, and physical and social skills. The assessment of character development is conducted holistically, flexibly, and contextually, involving cross-sector collaboration with government institutions and professionals. Major challenges include the diverse conditions of the children, limited family support, the constrained capacity of educators, and financial limitations. To address these issues, the orphanage implements individualized approaches, a tiered and inclusive mentoring system, cross-sector collaboration, and partnerships with private donors. This study recommends the development of adaptive, systemic, and sustainable strategies to optimally foster independence in children with intellectual disabilities.